Levels of toxic and essential metals in maternal and umbilical cord blood from selected areas of South Africa-results of a pilot study - Rollin, Halina B.; Rudge, Cibele Vieira Cunha [UNESP]; Thomassen, Yngvar; Mathee, Angela; Odland, Jon O. (Royal Soc Chemistry, 2009)
This pilot study uses concentrations of metals in maternal and cord blood at delivery, in seven selected geographical areas of South Africa, to determine prenatal environmental exposure to toxic metals. Samples of maternal and cord whole blood were analysed for levels of cadmium, mercury, lead, manganese, cobalt, copper, zinc, arsenic and selenium. Levels of some measured metals differed by site, indicating different environmental pollution levels in the regions selected for the study. Mercury levels were elevated in two coastal populations studied (Atlantic and Indian Ocean sites) with mothers from the Atlantic site having the highest median concentration of 1.78 mu g/L ranging from 0.44 to 8.82 mu g/L, which was found to be highly significant (p < 0.001) when compared to other sites, except the Indian Ocean site. The highest concentration of cadmium was measured in maternal blood from the Atlantic site with a median value of 0.25 mu g/L (range 0.05-0.89 mu g/L), and statistical significance of p < 0.032, when compared to all other sites studied, and p < 0.001 and p < 0.004 when compared to rural and industrial sites respectively, confounding factor for elevated cadmium levels was found to be cigarette smoking. Levels of lead were highest in the urban site, with a median value of 32.9 mu g/L (range 16-81.5 mu g/L), and statistically significant when compared with other sites (p < 0.003). Levels of selenium were highest in the Atlantic site reaching statistical significance (p < 0.001). All analysed metals were detected in umbilical cord blood samples and differed between sites, with mercury being highest in the Atlantic site (p < 0.001), lead being highest in the urban site (p < 0.004) and selenium in the Atlantic site (p < 0.001). To the best of our knowledge this pilot investigation is the first study performed in South Africa that measured multiple metals in delivering mothers and umbilical cord blood samples. These results will inform the selection of the geographical sites requiring further investigation in the main study.